Developing a conceptual framework for a citizen Science-based agroecology self-assessment tool - Mupangwa, Walter; Maharaj, Udhav; Taylor, Jim; Dickens, Chris; Choruma, Dennis; Pike, Trevor; Dirwai, Tinashe L.; Nyawira, Silvia; Geck, Matthias Samuel; Braithwaite, Isabella (Frontiers in Agronomy, 2025)
IntroductionAgroecology offers a promising approach to strengthen, and revolutionise, smallholder food and agricultural systems. Unfortunately, the assessment of agroecology impact at different scales and contexts is hindered by a lack of data and a lack of awareness of the potential of agroecology. Citizen science approaches are, however, demonstrating a knowledge revolution where learning is vested in the hands and tools of the farmers. The self-correcting mechanisms, that citizen science offers, enable the farmers to learn about and change their practices through the evidence they discover. In this way, the ability to change comes from within farmers’ experience and practices rather than farmers receiving information and knowledge from the outside. The purpose of this research work was to develop an accessible citizen science-based Agroecology Self-Assessment (ASA) tool framework.MethodsThis proposed ASA framework is purely conceptual, at this stage, and encompasses both physical and digital tools that can be used to assess agroecological practices and has the potential to address gaps related to agroecology performance assessments, data generation and knowledge-sharing. Furthermore, the proposed tool could lead to the development of a citizen science community of practice to empower smallholder farmers to collaborate and share both new and indigenous knowledge practices. Through fieldwork, the feasibility of using a mobile application to both collect data on various agroecological indicators, such as soil health, biodiversity, and water management, as well as socioeconomic factors related to agroecology was investigated.Results and discussionThe findings from the fieldwork showed that there is interest by smallholder farmers and agricultural extension officers in the use of citizen-science tools to complement and enhance agroecological practices. The conceptual design and framework for the ASA tool was developed using the information from a desktop-based literature review and findings from discussions with smallholder farmers, researchers and agricultural extension officers. It is envisaged that the ASA tool, once in operation, will provide smallholder farmers with personalised feedback based on household and field assessments, foster knowledge sharing and self-correcting mechanisms. Such applied practices enable, and strengthen, evidence-based decision-making. The study concludes that the ASA tool is undoubtably needed and should include relevant practical assessment tools.